Collaborative Instruction by Writing and Library Faculty: A Two-Tiered Approach to the Teaching of Scientific Writing - Deborah Huerta; Victoria E. McMillan (Issues in Science and Technology Librarianship)
We describe the results of six years of experimentation with the collaborative teaching of scientific writing to college undergraduates at both beginning and advanced levels. Our goal was to devise a two-course sequence for students interested in health and natural sciences, with emphasis on information literacy and analysis, effective reading, drafting and revising strategies. Beginning science students need help with many basic aspects of college-level writing and information-seeking skills, as well as an introduction to the most common types of writing assigned in introductory science courses -- the lab report and the short review paper. Advanced students are ready to learn sophisticated approaches to scientific information retrieval as well as the style and format of professional journal articles. They are also in a position to appreciate the ways in which scientific writing is molded and constrained by the scientific method, by the diversity of ways in which scientists communicate both formally and informally, and by the impact of the digital revolution on scholarly communication. Both courses are organized around peer review of student work-in-progress, with the submission of a portfolio of writing twice during the semester. We employ information technology as appropriate. Together we plan and teach all aspects of both courses in order to model the interrelated nature of research and writing. This collaboration by science and library faculty, we feel, holds exciting prospects for the future.